Teori Behaviorisme Burrhus Frederic Skinner dan Implementasinya dalam Meningkatkan Maharah Kalam - NAJA ALWI (Yayasan Daarul Qimmah Gorontalo, 2023)
The theory of behaviorism regarding the view of learning is the change in behaviorsm as a result of the interaction between stimulus and response. In other words, learning is the change experienced by students in terms of their ability to behave in new ways as a result of the interaction between stimulus and response. Based on this, researchers have developed B.F. Skinner's behaviorism theory and its implementation in enhancing the maharah kalam to make students understand and master the Arabic language better, and to reduce the low level of Arabic language proficiency in Indonesia. This research model utilizes literature review and employs qualitative descriptive analysis method. The research yields several maharah kalam learning techniques that can be implemented based on B.F. Skinner's perspective, namely: shaping behavior, generalization, discrimination and extinction, schedule of reinforcement, positive reinforcement, intermittent reinforcement, extinction, modeling, and token economy.